2021
DOI: 10.1021/acsbiomaterials.1c00047
|View full text |Cite
|
Sign up to set email alerts
|

β-Elemene Attenuates Fibrosis after Esophageal Endoscopic Submucosal Dissection via Modulating the HIF-1α/HK2/p38-MAPK Signaling Axis

Abstract: Esophageal fibrosis and stricture after endoscopic submucosal dissection (ESD) are serious postoperative complications. Previous evidence has highlighted an anticancer role of β-elemene in esophageal squamous cell carcinoma. This study put forward a hypothesis on the inhibitory effect of β-elemene on esophageal fibrosis after ESD and aimed to elaborate the underlying mechanisms. Our initial network pharmacology analyses determined hypoxia-inducible factor-1alpha (HIF-1α), hexokinase 2 (HK2), and p38MAPK in ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Hong et al demonstrated that β-elemene ameliorates esophageal fibrosis by reducing the expression of α-SMA, collagen I, and fibronectin [ 39 ]. We demonstrated that β-elemene similarly ameliorated renal tubular injury and fibrosis in the UUO model.…”
Section: Discussionmentioning
confidence: 99%
“…Hong et al demonstrated that β-elemene ameliorates esophageal fibrosis by reducing the expression of α-SMA, collagen I, and fibronectin [ 39 ]. We demonstrated that β-elemene similarly ameliorated renal tubular injury and fibrosis in the UUO model.…”
Section: Discussionmentioning
confidence: 99%
“…The up-regulation of HK under hypoxia enhances glycolysis, autophagy and epithelial-mesenchymal transformation ( Chen et al, 2018 ). The up-regulation of hexokinase can promote glycolysis by binding to the mitochondrial outer membrane and providing ATP for cell metabolism ( Hong et al, 2021 ). LDH can be divided into LDHA and LDHB subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has the potential to function as a nano-delivery drug to counteract tamoxifen-induced immunosuppression and thereby enhance chemoimmunotherapy [ 20 ]. Interestingly, β-elemene has been demonstrated to possess the efficacy of mitigating fibrosis in various tissues and organs, including esophageal fibrosis [ [21] , [22] , [23] , [24] ]. However, its specific mechanism in esophageal fibrosis remains unclear.…”
Section: Introductionmentioning
confidence: 99%